Digital Transformation: Changes in the Global Economic Paradigm in the Era of Digitalization - Azisah, Nur (Professorline, 2024)
The era of digitalization has fundamentally changed the global economic paradigm, presenting unprecedented opportunities and challenges. This research examines the impact of digital transformation on economic structure, labor markets and global business dynamics. Using a qualitative approach with secondary data analysis and literature study, this research reveals significant trends in digital technology adoption in various regions, shifts in the contribution of economic sectors to global GDP, and the evolution of demand for workforce skills. Results show a rapid increase in digital technology adoption, with gaps still existing between developed and developing countries. The information technology sector is emerging as a major contributor to economic growth, while demand for technology-related skills and soft skills is increasing sharply. The research also identifies critical policy challenges, including bridging the digital divide, managing workforce transitions, and designing effective regulatory frameworks. In conclusion, digital transformation demands rapid adaptation from all stakeholders and a collaborative approach to maximize benefits while mitigating emerging risks. The implications of this research include the need for continued investment in digital infrastructure, education system reform, and the development of a comprehensive national strategy to face the digital economy era.